The impact of electrolyte on adsorption at the air-water interface for ternary mixtures above the critical micelle concentration - Liley, J; Thomas, R; Penfold, J; Tucker, I; Petkov, J; Stevenson, P; Webster, J (American Chemical Society, 2017)
The composition of the air-water adsorbed layer of the ternary surfactant mixture, octaethylene monododecyl ether, C12E8, sodium dodecyl 6-benzene sulfonate, LAS, and sodium dioxyethylene glycol monododecyl sulphate, SLES, and of each of the binary mixtures, with varying amounts of electrolyte, has been studied by neutron reflectivity. The measurements were made above the mixed critical micelle concentration. In the absence of electrolyte adsorption is dominated by the nonionic component C12E8 but addition of electrolyte gradually changes this so that SLES and LAS dominate at higher electrolyte concentrations. The composition of the adsorbed layer in both binary and ternary mixtures can be quantitatively described using the pseudo-phase approximation with quadratic and cubic interactions in the excess free energy of mixing (GE) at both the surface and in the micelles. A single set of parameters fits all the experimental data. A similar analysis is effective for a mixture in which SDS replaces SLES. Addition of electrolyte weakens the synergistic SLES-C12E8 and LAS-C12E8 interactions, consistent with them being dominated by electrostatic interactions. The SLES-LAS (and SDS-LAS) interaction is moderately strong at the surface and is little affected by addition of electrolyte, suggesting that it is controlled by structural or packing factors. Most of the significant interactions in the mixtures are unsymmetrical with respect to composition, with the minimum in GE at the 1:2 or 2:1 composition. There is a small structural contribution to the LAS-C12E8 interaction that leads to a minimum intermediate in composition between 1:2 and 1:1 (LAS:C12E8) and to a significant residual GE in strong electrolyte.